Growth and rumen development in calves fed starter submitted to different processing. - Castro-Flores, Pamela; Elizondo-Salazar, Jorge Alberto (Agronomía Mesoamericana, 2012)
The objective of the study was to evaluate the effect of calf starter processing on growth and rumen development during the pre-weaning period. Twelve Holstein bull calves weighing on average 38 kg were used. Calves were randomly assigned to one of four treatments: ground, ground+forage, pelleted, and extruded. Feed intake, body weight, withers height, and hip height were recorded weekly. Calves were harvested at eight weeks of age and stomachs were collected to determine papillae length and width, and rumen wall thickness. Feed intake was different between pelleted and ground+forage treatments. At the end on the trial calves on the ground treatment had the highest intake. Body weight was not different between treatments. Calves on the pelleted and extruded treatments presented the highest withers height during the last two weeks of the trial. Hip height showed no differences between treatments. When examining weight of the stomach compartments no differences were found. Calves on the extruded treatment showed the lowest papillae height when compared to animals on the ground or ground+forage treatment. These results indicate that rumen development is affected by feed processing; however, other factors should be considered.